Removal of some heavy metals from aqueous solutions using natural wastes orange peel activated carbon - H. H. Ali, Mohamed; Abdel-Satar, Amaal M. (IJRDO-Journal of Applied Science, 2017)
The adsorption of heavy metals by various types of activated carbon originated from natural wastes is an effective, low-cost and innovative method for their removal from aquatic environments. This study aims to determine the applicability of adsorption isotherms models during the adsorbent activity of orange peel activated carbon for removal of Pb+2, Ni+2, Cr+3 and Cd+2 ions. The specific surface area, micropore area, and the effects of pH value, soaking time and dosage of orange peel activated carbon were investigated in this study. The optimum pH values for adsorption capacity and removal efficiency of heavy metal ions were 5 – 6. The optimum soaking time was 120 min for Pb+2, 210 min for Ni+2 and Cr+3 and 240 min for Cd+2 . The optimum adsorbent dosage for removal of the studied was 2 gm. The isotherm equilibrium studies confirmed that both Langmuir and Freundlich adsorption isotherms well fitted models and revealed that adsorption of metals ions is one layer adsorption and confirmed highly efficient orange peel activated carbon in the removal of heavy metals. The environmentally friendly origin of orange peel indicates that could use in many broad-scale, low cost-effective and alternative applications.